Sentiment Analysis of Southeast Asian Games (SEA Games) in Philippines 2019 Based on Opinion of Internet User of Social Media Twitter with K-Nearest Neighbor and Support Vector Machine - Muhammad Riefky; Wara Pramesti (Department of Mathematics, Hasanuddin University, 2020)
Sports events are an activity that is in great demand, especially the people of Southeast Asia. One of the most prestigious sporting events in the Southeast Asian region is the Southeast Asian Games (SEA Games). SEA Games is one of the sporting events held in the Southeast Asia region and is only held every two years involving eleven member countries of the Association of South East Asian Nations (ASEAN). The most SEA Games issues occurred on Twitter with 20,600 tweets. This is because the 2019 SEA Games event in the Philippines experienced many irregularities, one of which is the Rizal Memorium stadium, which has not been renovated until now. The purpose of this study is to obtain and compare the results of the accuracy of the classification of Twitter users' sentiments towards the 2019 SEA Games in the Philippines using k-nearest neighbor and support vector machine. The data used in this study comes from data from Twitter social media users who often use the hashtag